Polish Question in Russia in the Assessment of A.S. Budilovich - Tadeusz T. Kruczkowski (Славянский мир в третьем тысячелетии, 2023)
The article discusses the main viewpoints of the Russian historian and philologist Anton S. Budilovich on the Polish question in Russia. Budilovich was a dynamic personality and, at the same time, a prominent philologist, historian, publicist, and above all, an excellent administrator of science and education. The name Budilovich was widely known in the educated circles of contemporary society. He spent his entire life working in educational institutions in St. Petersburg, Nezhin, Warsaw, and Yuryev. Budilovich acquired work in the Russifi cation of Warsaw and Yuryev universities. The scholar’s views are considered against the background of the position generally inherent in Russian historiography. The topics studied by Budilovich were closely connected with the history of the Orthodox lands of the Polish–Lithuanian Commonwealth and the Western Russian (Belarusian and Ukrainian) issue. The scientifi c and socio-political views of Budilovich were influenced by both the nature of his education and the socio-political environment of what was then Western Russia. In general, Budilovich’s historical polonistics fully corresponded to the fundamental ideas of Russian historical polonistics of the nineteenth and early twentieth centuries: conservative and Slavophile in nature, and mostly anti-Western. The most important attribute of Slavic unity for Budilovich was the religious community of the Slavs and their common language. Orthodoxy seemed to him the foundation on which the Slavs exclusively could preserve their own identity. He explained Russia’s mission in Poland to be motivated by its desire to save the Poles from the Germanization that threatened them and to “bring to life” Polish moral and intellectual forces. The scholar was one of the last adherents of the Slavophile approach to history and a supporter of pan-Slavic ideas.